Analisis Stabilitas Keuangan Bank Mega Tbk Periode 2018-2025: Pengaruh BOPO dan CAR - Wardah Syafirah; Denny Hambali (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of operational efficiency and capital on financial stability at PT Bank Mega Tbk for the 2018–2025 period. Financial stability is proxied using the Z-Score, while internal bank factors are measured through the Operating Costs to Operating Income (BOPO) and the Capital Adequacy Ratio (CAR). The analytical method used was multiple linear regression with IBM SPSS version 30. The results show that both variables simultaneously have a significant effect on financial stability. Partially, capital has a positive and significant effect and is the most dominant determinant of financial stability, while operational efficiency, proxied by BOPO, has a negative and significant effect on financial stability. These findings imply that banking stability is strongly influenced by capital strength and the bank’s ability to manage operational efficiency. Therefore, strengthening the capital structure and controlling operational costs are key factors in maintaining a bank’s financial stability amidst economic dynamics.